2010
DOI: 10.1183/09031936.00116109
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to close-proximity air pollution and asthma and allergies in urban children

Abstract: The aim of this study was to evaluate the impact of urban air pollution, assessed through reliable indicators of exposure, on asthma and allergies in schoolchildren.A validated dispersion model combining data on traffic conditions, topography, meteorology and background pollution was used to relate 3-yrs averaged concentrations of major urban pollutants at the sites of schools to skin prick tests, exercise-induced asthma and reported asthma and allergies in 6,683 children (9-11 yrs) attending 108 schools rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
177
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(191 citation statements)
references
References 36 publications
5
177
1
8
Order By: Relevance
“…A study conducted in France also showed positive associations between exposure to PM2.5-10 and hospitalisation for respiratory infections in children [23]. Another French study, using a dispersion model, found positive associations between PM10 exposure and asthma and allergies in children [24].…”
Section: Discussionmentioning
confidence: 95%
“…A study conducted in France also showed positive associations between exposure to PM2.5-10 and hospitalisation for respiratory infections in children [23]. Another French study, using a dispersion model, found positive associations between PM10 exposure and asthma and allergies in children [24].…”
Section: Discussionmentioning
confidence: 95%
“…Using a cross-sectional design and an enhanced ISAAC protocol for outcomes, 6683 children in the French Six Cities Study were studied with exposures based on a 3-year dispersion model for each school address to assign individual school exposures [Penard-Morand et al 2010]. Asthma was significantly associated with benzene, SO 2 , PM10, NOx and CO levels; allergic rhinitis was only associated with PM10 levels.…”
Section: Air Quality and Respiratory Allergiesmentioning
confidence: 99%
“…A study of 4907 French children found associations of both lifetime and 1-year history of AD with NO x , CO, NO 2 , PM 10 , and benzene pollutants [101]; these are major urban pollutants believed to be primarily influenced by vehicular traffic. A US population-based study found the prevalence of childhood AD to be associated with mean annual NO 2 , sulfur dioxide (SO 2 ), and sulfur trioxide (SO 3 ), but inversely associated negatively with mean annual nitrate (NO 3 ), organic carbon (OC), PM 2.5 , and PM 10 [98].…”
Section: Air Pollutantsmentioning
confidence: 99%